The Anthropocene is shifting the paradigm of geosciences and science - Coudrain, Anne; Le Duff, Matthieu; Mitja, Danielle (Comptes Rendus. Géoscience, 2022)
Noting that humans are affecting the Earth’s envelopes, with geosciences becoming inseparable from social sciences and humanities, and acknowledging the increasing use of the word Anthropocene, the authors of this paper explore the possibility of a scientific paradigm shift. (1) Since the 17th century, modern science has developed in a context of naturalist worlding that favors its hegemony over other modes of existence and its paradigm of a quest to define the laws of nature. (2) Various manifestations attest to the emergence of a paradigm of knowledge diversity and the unravelling of the naturalist worlding. (3) The current boom in participatory science is a sign of this paradigm shift: through the fundamental changes to the Earth System that refer to it, the Anthropocene forces science to move towards action and interact with a society involved in adapting to changes and concerned with the threats to its territory’s habitability.